Synthesis, Absorption and Fluorescence Spectral Investigation of Porphyrazines with Eight 2-Naphthalenecarboxy Esters - Coskun, N. Yilmaz; Atak, O.; Kilicarslan, F. Aytan; Yalcin, S. M.; Guel, A. (POLISH CHEMICAL SOC, 2008)
New magnesium porphyrazines substituted with eight naphthalenecarboxy groups on the peripheral positions were synthesized through a stepped reaction; first, cyclotetramerization of 1,2-dicyano-1,2-bis(2-hydroxyethylthio)ethylene led to a porphyrazine formation which was subsequently esterified with 2-naphthoic acid. A metal-free derivative was prepared by treatment with trifluoroacetic acid. Metallo-porphyrazines were prepared by insertion of Zn(II), Co(II) and Ni(II) ions. These porphyrazines were characterized by elemental analysis, (1)H NMR, (13)C NMR, LC-MS, FT-IR, and UV-Vis spectral data. In addition, fluorescence emissions of the compounds with naphthalene were obtained and the emissions due to the naphthalene moieties covalently-bonded to the porphyrazine were partially quenched.
Keywords: porphyrazine; fluorescence; naphthalene; zinc; cobalt; nickel; TGA; FLUORENONE PENDANT ARMS; METAL-ION BINDING; ENERGY-TRANSFER; PORPHYRIN; DERIVATIVES; PHTHALOCYANINE; SUBSTITUENTS; MACROCYCLES; TRANSITION; Chemistry